(untitled) (Research, Society and Development, 2020)
The objective of this study was to reflect on the central pillars of the theories of the philosopher Thomas Kuhn, about the process of scientific revolutions and its relationship with the process of academic maturity. For this study, the authors intend to carry out a reflective study, of a descriptive and qualitative nature, recorded in book "A Estrutura das Revoluções Científicas", by Kuhn’s authorship. In addition, it is reflecting on the experiences of two authors who are guiding-counseling, and also, as educators, they do not teach illness since graduation, or doctorate. The reflections presented in this study showed that academic maturity has a relationship with the movement in what Kuhn calls a scientific revolution based on the following phases: pre-paradigmatic; normal science; crisis / revolution, new normal science and new crisis / revolution, demonstrating the approximation of these phases of the theory, with the academic experience, bringing possible answers about the relationships resulting from the personal / educational maturation. From the reflection, it was possible to conclude that, the propositions of the aforementioned philosopher, helps us to understand that for academic maturity to occur, these need to fit in a sequential and cyclical way, however, this maturity depends on the degree of the student’s relationship and educator and the educator-advisor’s view of their role in the educational process.